Surface Engineered Metal-Organic Frameworks (MOFs) Based Novel Hybrid Systems for Effective Wound Healing: A Review of Recent Developments - Fu, Luo-Qin; Chen, Xiao-Yi; Cai, Mao-Hua; Tao, Xiao-Hua; Fan, Yi-Bin; Mou, Xiao-Zhou (Frontiers in Bioengineering and Biotechnology, 2020)
Wounds present serious medical complications and their healing requires strategies that promote angiogenesis, deposition of collagen as well as re-epithelialization of wounds. Currently used conventional wound healing strategies have become less effective due to various issues associated with them. Thus, novel strategies are needed to be developed for early and effective healing of wounds. Metal-organic frameworks (MOFs), formed by linking of metal ions through organic bridging ligands, are highly tunable hybrid materials and have attracted more considerable scientific attention due to their charming and prominent properties such as abundant pore structures and multiple functionalities. Surface engineering of MOFs with unique ligands can overcome issues associated with conventional wound healing methods, thus resulting in early and effective wound healing. This review has been undertaken to elaborate wound healing, and the use of surface engineered MOFs for effective and rapid wound healing. The process of wound healing will be discussed followed by a detailed review of recent literature for summarizing applications of surface engineered MOFs for wound healing. MOFs wound healing will be discussed in terms of their use as antibacterial agents, therapeutic delivery vehicles, and dressing systems in wound healing.